2-6(-5t+-1)=

Simple and best practice solution for 2-6(-5t+-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-6(-5t+-1)= equation:


Simplifying
2 + -6(-5t + -1) = 0

Reorder the terms:
2 + -6(-1 + -5t) = 0
2 + (-1 * -6 + -5t * -6) = 0
2 + (6 + 30t) = 0

Combine like terms: 2 + 6 = 8
8 + 30t = 0

Solving
8 + 30t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 30t = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 30t = 0 + -8
30t = 0 + -8

Combine like terms: 0 + -8 = -8
30t = -8

Divide each side by '30'.
t = -0.2666666667

Simplifying
t = -0.2666666667

See similar equations:

| 90=x+(x-20) | | 37=2x-19 | | 3x+20-x=30 | | x+2.8=6.5 | | 110+3x-2=90 | | 4X-7=2(2X+7)-5 | | x/-3-5=3 | | 2X-7=2(2X+7)-5 | | y=16x+63 | | 240=0.5(x(30)) | | 16x^2+25-9=0 | | 2x+2(6x-9)=94 | | 14x+1=29 | | 8-7=2(2X+7)-5 | | sec(3x)=4 | | Y=100x-50 | | -2y-8=5y-1 | | 10x-13x+-5x=-15+8x | | 6x+3x-4=5 | | p/4-3=-2 | | 3n^2-25=-8 | | -6(1-x)=42 | | ln^(x)=(4/3) | | X-6+2x+3=90 | | -1-2x=-(-x+7) | | -5(3+4x)=65 | | 2(u+13)=86 | | 7(n-4)-6=-40+n | | 9x+8x-6x-5=6 | | 3x+11=-9-13 | | y=(x-1)(x+2)(x-4+3i) | | 10n^2+20n-76=4 |

Equations solver categories